Dampak Pelayanan Yang Dilakukan di Polres Tangerang Selatan Terhadap Pertumbuhan Iman dan Pertobatan Tahanan - Prana Winata Ginting; Yusup Rogo Yuono (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Criminals who are being held in the South Tangerang Police detention center really need attention and care from others. One of them is service to prisoners. Regarding service to prisoners, there are many journals that discuss this, for example in the Correctional Institution (Lapas). In the South Tangerang Police itself, there is no journal for service to prisoners, therefore I want to explore this further. So this journal discusses service to prisoners. This study uses a qualitative method with observation and interviews. This study aims to provide information on the implementation of service to prisoners, this is spiritual service and the impact of service. Service at the South Tangerang Police Resort is very helpful in increasing the growth of faith and repentance. Because service can encourage and help faith grow further, so that prisoners can accept the circumstances they experience and that faith leads them to repentance to become a righteous person.